Que nul ne puisse se plaindre d'avoir été écarté - Roger Monjo (Nantes Université, 2014)
It may be beneficial to adopt an approach inspired from moral minimalism in order to design a school ethics adapted to the current conditions of pedagogical action. Indeed, the prevailing discourse in that matter is steeped in paternalistic and moralistic injunctions. However, one may wonder about the benefits to be expected from such an approach insofar as the content of moral minimalism is itself minimalist. « No one should have to complain that they have been excluded » expresses Condorcet's opposition to compulsory school attendance, a striking anticipation of the central rule of minimalist ethics (« do not harm others »). Nevertheless, by reducing Condorcet's phrase to this strict negativity, one may run the risk of losing sight of his more solid moral intuitions, which could still inspire the ethics of teaching today. That is the reason why we will also discuss how alternative approaches (such as the theories of care or of recognition) might contribute to the development of such an ethics.